The effects and mechanism of discounting unit price - Khan, Huda; Saeed, Muhammad Rashid; Bellman, Steven; Lee, Richard (Emerald, 2024)
Purpose Supermarket promotions typically use a standard label, which displays the regular price, discounted price and discounted unit price. Visits to supermarkets across multiple countries found that none used a price label that also contains the regular (i.e. pre-discounted) unit price. This study aims to investigate the effectiveness of a dual unit-price label that includes the regular unit price as a reference price, and what underpins its efficacy in enhancing promotion attractiveness. Design/methodology/approach The authors executed four studies, supported by three supplemental studies. Study 1 established external validity through a natural instore experiment. Studies 2 and 3 tested the dual unit-price label with different pack sizes and assortment sizes, respectively. Finally, Study 4 tested the underpinning mechanism of the efficacy of the dual unit-price label. Findings In Study 1, daily sales records over four weeks showed that dual unit-price label promotions had larger sales volume than standard-label promotions. Study 2 showed a larger pack size, a heuristic cue for greater economy and increased preference for dual unit-price label promotions. Study 3 similarly found that the dual unit-price label was preferred more as cognitive load was increased by assortment size. Finally, Study 4 demonstrated the dual processing of the dual unit-price label, using a conscious preference measure (information provided) and an unconscious implicit attitude test. Research limitations/implications Unit-price research has mainly considered a cognitive process. The authors demonstrated the importance of considering a heuristic process. Practical implications Supermarkets can use this simple and yet effective tool to improve promotion effectiveness. Originality/value This study demonstrates that the dual unit-price label is a new and easy tool to enhance sales promotions, which academic research and managerial practice had never considered previously.
Keywords: Unit price; shelf labels; sales promotions; dual processing; heuristic cues